2017
DOI: 10.1093/ptj/pzx078
|View full text |Cite
|
Sign up to set email alerts
|

The Pelvic Girdle Questionnaire: Responsiveness and Minimal Important Change in Women With Pregnancy-Related Pelvic Girdle Pain, Low Back Pain, or Both

Abstract: The PGQ showed acceptable responsiveness in women with PGP, low back pain, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 46 publications
1
24
1
Order By: Relevance
“…An explanation for this is that both pelvic girdle questionnaire and ODI are related to pain severity and its consequences. The assumption that pelvic girdle questionnaire is more sensitive and specific to consequences from PGP [13], was corroborated when the whole range of the scale was used in pelvic girdle questionnaire (0-93) as compared to ODI (0-64). In addition, the Swedish version of the pelvic girdle questionnaire showed no floor or ceiling effects, which strengthens its validity.…”
Section: Validationmentioning
confidence: 88%
See 2 more Smart Citations
“…An explanation for this is that both pelvic girdle questionnaire and ODI are related to pain severity and its consequences. The assumption that pelvic girdle questionnaire is more sensitive and specific to consequences from PGP [13], was corroborated when the whole range of the scale was used in pelvic girdle questionnaire (0-93) as compared to ODI (0-64). In addition, the Swedish version of the pelvic girdle questionnaire showed no floor or ceiling effects, which strengthens its validity.…”
Section: Validationmentioning
confidence: 88%
“…Previous studies have shown that self-reported PGP correlates well with clinically examined PGP, and we can thereby assume that the majority suffered from PGP [29,30]. In addition, pelvic girdle questionnaire is proposed as a suitable instrument for studies on LBP and PGP [13].…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used ROC curves to examine cutoff values for the OMQ scale change scores (de Vet et al, 2006) The perceived improvement of movement quality on the GPE was used as an anchor (de Vet et al, 2011), which required the choice of a sensible cutoff point of important change (Stuge, Krogstad Jenssen, & Grotle, 2017). There is debate about whether the category 'a little improved' should be considered as change (de Vet et al, 2007;Demoulin, Ostelo, Knottnerus, & Smeets, 2010;Jaeschke et al, 1989;Wyrwich et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between PROM change scores and GRC scale scores were assessed by calculating Spearman's rank correlation coefficients. Correlation was interpreted as high (> 0·5), moderate (0·3–0·5) or low (< 0·3), based on previous studies and guidelines for assessing responsiveness . The next hypotheses (5, 6, 7) concerned the mean PROM change scores of improved, unchanged and worsened patients according to the associated GRC scale, namely the GRC scale measuring a similar construct.…”
Section: Methodsmentioning
confidence: 99%